An investigation of the relationship between temporomandibular disorder with upper quadrant posture - Ergezen, Gizem; Şahin, Murat; Algun, Zeliha Candan (Springer London Ltd, 2018)
[Abstract Not Available]
WCO-IOF-ESCEO World Congress on Osteoporosis, Osteoarthritis and Musculoskeletal Diseases -- APR 19-22, 2018 -- Krakow, POLAND
WOS: 000440102401270
Keywords: Temporomandibular; Investigation; Upper Quadrant Posture